2003
DOI: 10.3928/0098-9134-20031101-09
|View full text |Cite
|
Sign up to set email alerts
|

BedSAFE: A Bed Safety Project for Frail Older Adults

Abstract: In response to heightened awareness of patient safety, restraint reduction, and the potential for life-threatening entrapment caused by bed rails, a quality improvement program entitled BedSAFE was conducted to systematically and safely decrease the use of bed rails in three nursing home care units. This article describes an interdisciplinary process of individualized patient assessment, selection of appropriate alternatives for residents, compliance monitoring, training, and monitoring of patient outcomes inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Whilst medical practitioners play a key role in authorizing the use of restraint, they appeared to have minimal capacity to comprehensively assess the need for restraint through observing residents at different times of the day or by consulting with family members. While the research literature often recommends an interdisciplinary team approach to assessing the need for restraint (Hoffman et al 2003), teams at the participating facilities usually comprised nursing, personal care and medical practitioners and family members. The use of allied healthcare services, such as (but not limited to) physiotherapy, occupational therapy and neuropsychology, for restraint assessment was minimal despite these staff having a broad range of skills relevant for addressing residents’ needs such as developing exercise programmes for improving strength and reducing falls.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst medical practitioners play a key role in authorizing the use of restraint, they appeared to have minimal capacity to comprehensively assess the need for restraint through observing residents at different times of the day or by consulting with family members. While the research literature often recommends an interdisciplinary team approach to assessing the need for restraint (Hoffman et al 2003), teams at the participating facilities usually comprised nursing, personal care and medical practitioners and family members. The use of allied healthcare services, such as (but not limited to) physiotherapy, occupational therapy and neuropsychology, for restraint assessment was minimal despite these staff having a broad range of skills relevant for addressing residents’ needs such as developing exercise programmes for improving strength and reducing falls.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies confirmed that education alone is not enough to ensure a reduction in the use of restraints (Huizing et al, 2009a;Pellfolk et al, 2010;Testad et al, 2010). The availability of alternative interventions seems to be an important additional prerequisite for eliminating restraint use (Becker et al, 2003;Capezuti et al, 1999;Freeman, 2004;Hoffman et al, 2003). In some countries such as Denmark, Scotland and the US belt restraint use is only permitted under strict conditions (Hamers and Huizing, 2005).…”
Section: Introductionmentioning
confidence: 94%
“…In 7 studies, no factors were identified [31,34,50,58,65,78,81] and in two, it was unclear [44]. Most studies reporting factors, discussed multiple individual factors (range = 1-7, average = 2.3) across multiple domains (range = 1-4, average = 2.0).…”
Section: Description Of Contributory/associated Factorsmentioning
confidence: 99%